Trade-Related Policy Responses to the Crisis : A Stock Taking - Evenett, Simon; Hoekman, Bernard; Cattaneo, Olivier (World Bank, Washington, DC, 2012)
The world is facing the most severe global economic crisis since the great depression of the 1930s. For the first time since World War two, World Bank projections for annual economic growth show that world gross domestic product (GDP) will decline 2.9 percent in 2009 and growth in developing countries will fall to 1.2 percent from 5.9 percent in 2008. Excluding China and India, other developing nations' economies will shrink on average by 1.6 percent. Net private capital flows to developing countries will likely turn negative in 2009 a more than $800 billion drop from the 2007 peak. The decline in global foreign direct investment (FDI) flows that started in 2008 will deepen and spread to the developing world, with overall inflows projected to fall some 30 percent compared to 2008, the first time FDI has fallen more than 10 percent in a year since 1986. The value of remittances, perhaps the most stable source of external financing for developing countries, is expected to drop by at least 5 percent this year.